STUDI OPTIMASI TEKNIS OPERASIONAL PENGUMPULAN DAN PENGANGKUTAN SAMPAH DENGAN MODEL SIMULASI (Studi Kasus Kecamatan Mengwi, Kabupaten Badung Tahun 2004-2024) - Arnatha, I Made (Jurnal Ilmiah Teknik Sipil; Vol. 16, No. 1 Januari 2012, 2012)
Abstract : Collecting and transporting waste are a part of waste management problems found in Mengwi District, Badung Regency. The study objective is to optimize and to increase efficiency of waste collection and transportation management using simulation models to improve public services. The simulation results show that in 2004 for a total of 281.19 m 3 /day of waste and it required 5 units of dump trucks, 12 units of containers, three units of armroll trucks, 94 units of carts and three units of sorting bins. In 2014, total waste would be 322.11 m 3 /day and it requires 5 units of dump trucks, 12 units of containers, 6 units of armroll trucks, 107 units of wagon and three units of sorting bins.  In 2024 there would be a total waste of 371.49 m 3 /day and it requires 6 units of dump trucks, 21 units of containers, 7 units of armroll trucks, 124 units of wagons and 4 units of sorting bins.
Keywords: Optimalisasi dan efisiensi, manajemen transportasi, model simulasi